Exploring the relationship between physical activity and Inhibitory Function in College Students with depressive symptoms through EEG - Zhao Jinlei; Si Yanran; Ding Feng; Jia Shuqi; Liu Cong; Wen Haiyan (Scientific Reports)
Abstract This study aims to examine the relationship between physical activity and inhibitory function in college students with depressive symptoms and to explore the role of resting EEG as a mediator in this relationship. Specifically, it analyzes how physical activity correlates with inhibitory function and identifies potential routes through which physical activity impacts inhibitory function. A cross-sectional study was conducted involving 154 college students with depressive symptoms. Participants completed the Basic Information Questionnaire, the Beck Depression Inventory-II, and the Physical Activity Rating Scale. Five-minute EEG signals were recorded, and participants performed behavioral tasks to assess inhibitory function. Data were analyzed using independent samples t-tests, χ2 tests, Pearson correlation analysis, and structural equation modeling. Significant differences were found between the adequate and inadequate physical activity groups in BDI scores and response inhibition (P < 0.05). There was a significant positive correlation between physical activity and the average accuracy rate on No-go tasks (r = 0.281, P < 0.001) in students with depressive symptoms. Delta and beta1 lateralization in the central, parietal, and temporal regions were significantly positively correlated with both physical activity and response inhibition (r = 0.20, r = 0.38, both P < 0.05). Both direct and mediating effects were significant, with direct effects accounting for 67.80% of the total effect (B = 0.141, 95% CI: 0.013–0.287) and mediating effects accounting for 32.20% of the total effect (B = 0.067, 95% CI: 0.029–0.136). Gender did not significantly moderate the relationship between physical activity and response inhibition (P > 0.05). There is a close relationship between physical activity, specific EEG indicators, and response inhibition. The central, parietal, and temporal regions serve as potential routes linking physical activity and response inhibition. Delta band lateralization (in the central, parietal, and temporal regions) may be the route through which physical activity influences response inhibition.